EVALUATION OF THE EFFECTIVENESS OF THE NEW AMINO ACID DRUG IN EXPERIMENTAL PROTEIN-ENERGY DEFICIENCY - Karimov, H.Ya.; Shevchenko, L.I.; Alimov, T.R.; Isroilov, A.A.; Ruziev, U.S.; Lubentsova, O.V. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To evaluate the effectiveness of the new amino acid remedy for correcting homeostasis disorders in a protein starvation model. Material and Methods: The model of protein starvation was reproduced in 60 male rats weighing 180-200 g, which were divided into four groups of 15 animals each: group 1 (control) – intact animals, 2nd, 3rd and 4 1st — protein-free diet, starting from the 11th day, animals of the 3rd group were injected with the comparison drug infezol 40, 4th – a new blood substitute at a dose of 10 ml/kg of body weight. Results: A new blood substitute restores protein, energy metabolism and electrolyte balance. The studied drug and infezol 40 restored the mass, protein metabolism, and electrolyte balance in approximately the same way over 10 days. However, when using a new blood substitute, energy metabolism was restored to a greater extent due to the antioxidant complex with energy activity. Conclusions: The use of a new blood substitute restores the parameters of protein and energy metabolism, as well as electrolyte balance, exceeding the effectiveness of infezol-40.